Pengaruh Konsumsi Madu terhadap Lama Persalinan Kala I dan Kala II - Rosmadewi Rosmadewi; Ranny Septiani (Jurnal Kesehatan, 2021)
The proportion of incidence of prolonged labor is 4,3 and is the second order of birth disorders or complications after premature rupture of membranes. The problem in this study was that 9% of women who gave birth were referred to the hospital because they experienced prolonged labor/labor was not advanced. This study aims to determine the effect of honey consumption on stage I and stage II labor duration in third-trimester multigravida pregnant women at PMB Karang Anyar Community Health Center, South Lampung Regency in 2019. This type of research is a quantitative (analytical) research method using a true experimental design with a post-test design only control group design. The subjects of the study were 90 third trimester multigravida, pregnant women. Data collection uses primary data. Univariate data analysis using percentages and bivariate analysis using chi-square. The results showed that there was an effect of giving honey consumption to third-trimester multigravida pregnant women on the first stage of labor with a p-value of 0,05 and there was an effect on the duration of labor in the second stage with a p-value of 0,02. Midwives as service providers to pregnant women and women who give birth advise mothers to consume honey 2-3 tablespoons 2 times a day from 34 weeks of gestation for good uterine contractions and increase the strength of the mother to push during the labor process.